Indigofera vicioides Jaub. & Spach (Fabaceae): a new distributional record for the flora of the Eastern Ghats, India - Devanathan, Krishnamoorthy; Dhatchanamoorthy, Narayanasamy (Biodiversity: Research and Conservation, 2022)
Indigofera vicioides Jaub. & Spach (Fabaceae) is a paleotropical species and a rarely found legume of the Southern India. This was the first time it has been recorded in the Eastern Ghats of Tamil Nadu. This article provides a detailed description of this finding together with images and field notes.